Complexation of bis‐crown stilbene with alkali and alkaline‐earth metal cations. Ultrafast excited state dynamics of the stilbene‐viologen analogue charge transfer complex. (31st August 2017) - Volchkov, Valery V.; Rusalov, Mikhail V.; Gostev, Fedor E.; Shelaev, Ivan V.; Nadtochenko, Viktor A.; Vedernikov, Artem I.; Efremova, Asya A.; Kuz'mina, Lyudmila G.; Gromov, Sergey P.; Alfimov, Michael V.; Ya. Melnikov, Mikhail
Abstract: The complex formation of bis(18‐crown‐6)stilbene (1 ) and its supramolecular donor‐acceptor complex with N, N ′‐bis(ammonioethyl) 1, 2‐di(4‐pyridyl)ethylene derivative (2 ) with alkali and alkaline‐earth metal perchlorates has been studied using absorption, steady‐state fluorescence, and femtosecond transient absorption spectroscopy. The formation of1 ∙M n + and1 ∙(M n + )2 complexes in acetonitrile was demonstrated. The weak long‐wavelength charge‐transfer absorption band of1 ·2 completely vanishes upon complexation with metal cations because of disruption of the pseudocyclic structure. The spectroscopic and luminescence parameters, stability constants, and 2‐stage dissociation constants were calculated. The initial stage of a recoordination process was found in the excited complexes1 ∙M + and1 ∙(M + )2 (M = Li, Na). The pronounced fluorescence quenching of1 ·2 is explained by very fast back electron transfer ( τ et = 0.397 ps). The structure of complex1 ·2 was studied by X‐ray diffraction; stacked (1 ·2 ) m polymer in which the components were connected by hydrogen bonding and stacking was found in the crystal. These compounds can be considered as novel optical molecular sensors for alkali and alkaline‐earth metal cations. Abstract : A decrease in the 3 characteristic relaxation times of complex1 ·2 with decreasing length of the ammonioalkyl N ‐substituents of the acceptor was demonstrated by femtosecond differential absorption spectroscopy.